The Evaluation of Cooperative’s Role in Soybean Supply Chain: A Case Study on Tofu and Tempeh Cooperatives in Indonesia - Susilowati, Etty; Oktaviani, Rina; Arifin, Bustanul; Arkeman, Yandra (UI Scholars Hub, 2015)
This study aimed to analyze and evaluate the extent of relationship between the soybean demand in a region and the number of cooperatives in the area, as well as the extent of relationship between the number of cooperative members (tofu and tempeh producers) and the number of cooperatives in the area. This study uses a quantitative approach based on primary data, later processed using Pearson correlation method. The results of data processing show that there is no significant relationship between the number of cooperatives and the number of producers. Furthermore, there is also no significant relationship between the number of cooperatives and existing soybean demands. This indicates the low role of cooperatives in the national soybean supply chain at the present. Therefore, there are two policy options that can be made. First, a radical policy, i.e. to leave out PRIMKOPTI in soybean supply chain at all. Second, the still mainstream policy, i.e. to still involve PRIMKOPTI, thus in order to make long-term programs in soybean business administration run well, PRIMKOPTI should be institutionally empowered and strengthened to achieve its business resilience.